Species richness and abundance of bats in fragments of the stational semidecidual forest, Upper Paraná River, southern Brazil - Ortêncio-Filho,H. (2009)
The Upper Paraná River floodplain is inserted in a region of the Mata Atlântica biome, which is a critical area to preserve. Due to the scarcity of researches about the chiropterofauna in this region, the present study investigated species richness and abundance of bats in remnants from the stational semidecidual forest of the Upper Paraná River, southern Brazil. Samplings were taken every month, from January to December 2006, using 32 mist nets with 8.0 x 2.5 m, resulting in 640 m²/h and totaling a capture effort of 87,040 m²/h. In order to estimate the species richness, the following estimators were employed Chao1 and Jack2. During the study, a total of 563 individuals belonging to 17 species (Artibeus planirostris, Artibeus lituratus, Carollia perspicillata, Platyrrhinus lineatus, Sturnira lilium, Artibeus fimbriatus, Myotis nigricans, Desmodus rotundus, Artibeus obscurus, Noctilio albiventris, Phylostomus discolor, Phylostomus hastatus, Chrotopterus auritus, Lasiurus ega, Chiroderma villosum, Pygoderma bilabiatum and Lasiurus blossevillii) were captured. The estimated richness curves tended to stabilize, indicating that most of the species were sampled. Captured species represented 10% of the taxa recorded in Brazil and 28% in Paraná State, revealing the importance of this area for the diversity of bats. These findings indicate the need to determine actions aiming to restrict human activities in these forest fragments, in order to minimize anthropogenic impacts on the chiropterofauna.